1979
DOI: 10.1111/j.1526-4610.1979.hed1902078.x
|View full text |Cite
|
Sign up to set email alerts
|

Tranquilizers and Mood Elevators in the Treatment of Migraine: An Analysis of the Migraine Foundation Questionnaire

Abstract: SYNOPSIS A sample of 1,500 self‐report mailed questionnaires distributed by the Migraine Foundation was analyzed To provide basic information on a large number of migraine sufferers in Canada, and more specifically to examine the extent of use and the perceived efficacy of tranquilizers and mood elevators by migraine sufferers. Data were presented on family history, headache history and type of migraine, triggers, physicians/specialist contacts, the extent and efficacy of both drug and non‐drug treatments, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Commonly used drugs for preventive treatment of migraine are tricyclic antidepressants, especially amitriptyline, and beta-blockers. [1][2][3][4][5][6][7][8][9] The efficacy of amitriptyline has already been established by earlier clinical studies. 1-4 However, this drug often causes side effects, that are not tolerated well by a significant percentage of migraineurs.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used drugs for preventive treatment of migraine are tricyclic antidepressants, especially amitriptyline, and beta-blockers. [1][2][3][4][5][6][7][8][9] The efficacy of amitriptyline has already been established by earlier clinical studies. 1-4 However, this drug often causes side effects, that are not tolerated well by a significant percentage of migraineurs.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine patients most often identified stress-related variables as responsible for the onset of their migraine headaches. 1 Bakal (1975) reviewed the literature on precipitants of headaches and similarly concludes that headaches (including migraine headaches) are a physiological reaction of stressful stimulation. Some 30 years ago, Wolff (1948) emphasized the role of stress in bringing on migraine headaches and felt that a major point of treatment was "... to help the individual understand the basis of his tension, the factors in his life that aggravate it, and to aid him in resolving his conflicts."…”
Section: Introductionmentioning
confidence: 99%
“…Even though such evidence for the efficacy of stress-related treatment exists, only a small percentage of migraine headache sufferers are ever exposed to this type of treatment regimen, whereas medication is frequently employed. 1,15 There are several reasons that could account for the relative prevalence of medication and the paucity of stress-related treatment. First, the availability of stress-related migraine treatment programs would be limited to larger metropolitan areas and thus would not be available to individuals who live in suburban or rural settings.…”
Section: Introductionmentioning
confidence: 99%
“…(Headache 29:352-357, 1989) Numerous studies have found emotional reactivity to be a precipitating factor for migraine headaches. [1][2][3][4][5][6][7][8][9] In cognitive-behavioral therapy the aim of treatment is to help people learn to modulate those maladaptive attitudes, appraisals, expectations and behaviors which contribute to anxiety and distress and which may, therefore, play a role in the precipitation and exacerbation of headaches. Several studies have demonstrated the efficacy of this approach for the treatment of migraine headaches.…”
mentioning
confidence: 99%